Quantitative pharmacokinetic analyses of anterior and posterior elimination routes of intravitreal anti-VEGF macromolecules using published human and rabbit data. (September 2022) - Lamminsalo, Marko; Urtti, Arto; Ranta, Veli-Pekka
Abstract: The purpose of this study was to evaluate the contribution of the anterior elimination route for four anti-vascular endothelial growth factor (anti-VEGF) macromolecules (aflibercept, bevacizumab, pegaptanib and ranibizumab) after intravitreal injection using published human and rabbit data and three previously described pharmacokinetic (PK) modeling methods. A PubMed search was used to identify published studies with concentration-time data. The data were utilized only if the intravitreally injected drugs were used as plain solutions and several criteria for a well-performed PK study were fulfilled. The three methods to analyze rabbit data were (1) the equation for vitreal elimination half-life based molecular size assuming anterior elimination, (2) Maurice equation and plot for the ratio of aqueous humor (AH) to vitreal concentration assuming anterior elimination, and (3) the equation for amount of macromolecule eliminated anteriorly based on the area under the curve in AH. The first and third methods were used for human data. In the second and third methods, AH flow rate is a key model parameter, and it was varied between 2 and 3 μl/min. The methods were applied to data from 9 rabbit studies (1 for aflibercept, 5 for bevacizumab, and 3 for ranibizumab) and 5 human studies (1 for aflibercept, 3 for bevacizumab, and 1 for ranibizumab). Experimental half-lives of anti-VEGF macromolecules in both vitreous and aqueous humor were close to those calculated with the equations for vitreal elimination half-life in humans and rabbits. Rabbit data analyzed with Maurice plot indicated that the contribution of anterior elimination was usually at least 75%. In most human and rabbit studies, the calculated percentage of anterior elimination was at least 51%. Variability between studies was extensive for bevacizumab and ranibizumab. The results suggest that the anterior elimination route dominates after intravitreal injection of anti-VEGF macromolecules. However, the clinical data are sparse and variability is extensive, the latter emphasizing the need of proper experimental design. Highlights: Intravitreal injections of anti-VEGF macromolecules are widely used globally. Their anterior and posterior elimination routes have not been studied systematically. Simple pharmacokinetic equations can be used to assess the elimination routes. The anterior route dominates for intravitreally injected anti-VEGF macromolecules.